REAKSI PASAR TERHADAP PENGUMUMAN PENINGKATAKN LEVERAGE DI BURSA EFEK INDONESIA - Elsya Meida Arif (Fakultas Ekonomi Universitas Borobudur, 2015)
This study was conducted to demonstrate empirically the market reaction to the announcement of the addition of the company’s leverage by issuing bonds. The sample used in this study is an event announcement of bond issuance period 2007-2010. The method used is the event study method using t-test and paired sample t-test. Calculation abnormal return is calculated by two alternative methods is market model and market adjusted model. The average abnormal stock returns before the announcement is no different to the average abnormal return time of the events and after the announcement. Keywords : the addition of leverage, the issuance of bonds, abnormal return, event study.